2016
DOI: 10.1007/s00213-016-4470-z
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing properties of an intermittent, low dose of ketamine in rats: effects of sex and cycle

Abstract: Rationale Repeated intermittent exposure to ketamine has rapid and long-lasting antidepressant effects, but the abuse potential has only been assessed at high doses. Furthermore, while females are more susceptible to depression and more sensitive to ketamine’s antidepressant-like effects, the abuse potential for ketamine in females is unknown. Objectives The objectives of this study are to determine the reinforcing properties of low-dose intermittent ketamine in adult rats of both sexes and determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 35 publications
3
25
1
Order By: Relevance
“…It is possible the observed effect is due to stage of estrous cycle as all females used in the present study were tested and administered ketamine in diestrous 1. A recent study from our lab showed cycle-dependent effects with acquisition of ketamine in a self-administration model, demonstrating that female rats in diestrous 1 do not acquire ketamine self-administration over ten sessions whereas males and proestrous females do (Wright et al , 2016). However, more studies examining cycle-dependent effects on NAc protein expression following ketamine administration are necessary to fully elucidate sex differences in protein expression following repeated ketamine injections.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible the observed effect is due to stage of estrous cycle as all females used in the present study were tested and administered ketamine in diestrous 1. A recent study from our lab showed cycle-dependent effects with acquisition of ketamine in a self-administration model, demonstrating that female rats in diestrous 1 do not acquire ketamine self-administration over ten sessions whereas males and proestrous females do (Wright et al , 2016). However, more studies examining cycle-dependent effects on NAc protein expression following ketamine administration are necessary to fully elucidate sex differences in protein expression following repeated ketamine injections.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible that estrous cycle could influence pharmacokinetic parameters of ketamine over repeated administration of a low dose. For example, estrous cycle appears to influence both maintenance of intravenous ketamine self-administration and reinstatement to ketaminepaired cues in rats (Wright et al, 2017). While pharmacokinetic differences between proestrus and diestrus rats are not apparent after a single systemic injection of low-dose ketamine, one cannot exclude the possibility that cycle-dependent reinforcing properties of ketamine following repeated administration (intravenous or otherwise) are influenced by pharmacokinetics.…”
Section: Sex Differences In Ketamine Pharmacokinetics In Ratsmentioning
confidence: 99%
“… Treatment Regimen Behavioral Response Molecular Change References Male Adult 100 μg per inf i.v. 1x/4 days ↑ FR1 self-administration n/a ( Wright et al, 2017 ) ↑ cue-induced reinstatement 2.5 mg/kg i.p. 1x/2 days no change ↑NAc ΔfosB ( Schoepfer et al, 2017 ) Weekly no change ↑ NAc shell spines ( Strong et al, 2017 ) 5 mg/kg i.p.…”
Section: The Addictive Potential Of Repeated Low-dose Ketamine Infusimentioning
confidence: 99%
“… Daily ↑ locomotor sensitization n/a ( Wiley et al, 2008 ) ↑ CPP n/a ( Li et al, 2008 ) 1x/2 days ↑ locomotor sensitization ↑ NAc ΔfosB ( Schoepfer et al, 2017 ) ↑ CPP Female Adult 100 μg per inf i.v. 1x/4 days ↑ FR1 self-administration (proestrous) n/a ( Wright et al, 2017 ) ↑cue-induced reinstatement (proestrous) ↓FR1 self-administration (diestrous) ↓ cue-induced reinstatement (diestrous) 2.5 mg/kg i.p. 1x/2 days no change ↑NAc ΔfosB ( Schoepfer et al, 2017 ) Weekly ↑ locomotor sensitization (diestrous) ↑ NAc shell spines ( Strong et al, 2017 ) 5 mg/kg i.p.…”
Section: The Addictive Potential Of Repeated Low-dose Ketamine Infusimentioning
confidence: 99%
See 1 more Smart Citation